2016
DOI: 10.1080/2162402x.2016.1219008
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of epigenetic therapy and immunity in locally recurrent or metastatic estrogen receptor-positive breast cancer: Correlative analysis of ENCORE 301, a randomized, placebo-controlled phase II trial of exemestane with or without entinostat

Abstract: Entinostat, a class I-selective histone deacetylase inhibitor, has shown promising activity in ENCORE 301, a randomized, placebo-controlled, phase II trial of exemestane with or without entinostat in women with locally recurrent or metastatic estrogen receptor-positive breast cancer progressing on a nonsteroidal aromatase inhibitor. ENCORE 301 showed an 8.3-mo improvement in median overall survival among patients who received entinostat. We investigated the impact of entinostat on immune subsets with CD40, HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…Recent reports suggest that HDAC inhibition alters the cytokine release and may change the function of innate immune cell infiltrates in the tumor microenvironment (6,8,12,35). Interestingly, correlative studies performed in breast cancer patients receiving entinostat showed a decrease in both monocytic and granulocytic MDSCs (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports suggest that HDAC inhibition alters the cytokine release and may change the function of innate immune cell infiltrates in the tumor microenvironment (6,8,12,35). Interestingly, correlative studies performed in breast cancer patients receiving entinostat showed a decrease in both monocytic and granulocytic MDSCs (35).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, correlative studies performed in breast cancer patients receiving entinostat showed a decrease in both monocytic and granulocytic MDSCs (35). In our experimental conditions, we actually observed an increase in both monocytic and granulocytic subsets of the MDSC population.…”
Section: Discussionmentioning
confidence: 99%
“…Entinostat, like domatinostat a class Iselective HDACi, was shown to reduce the number and function of MDSCs in murine models in which combination therapies with checkpoint inhibitors were evaluated [48]. Based on this mode of action, peripheral MDSCs were evaluated in advanced breast cancer patients treated with a combination of entinostat and exemestane [21]. Blood samples collected after two weeks of therapy revealed significantly decreased MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although epigenetic drugs are being evaluated in combination with immunotherapy in several clinical trials, translational data on the immunomodulatory effects of class I-selective HDACis are scarce. In breast cancer patients, the number of peripheral MDSCs was significantly reduced upon treatment with the HDACi entinostat and the aromatase inhibitor exemestane [21].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HDAC inhibition has been shown to increase PD-L1 expression in preclinical models, including in combination with a demethylating agent 29, 30 . Furthermore, there is both preclinical and clinical evidence that entinostat may affect myeloid suppressive derived cells 31, 32 . Thus, over the next years, several clinical trials will test novel combinations of immunotherapies for ccRCC including checkpoint inhibitors, vaccines, adoptive T-cell therapy and T-cell agonists 33 , and HDAC inhibitors may provide an additional tool to modulate the immune response more effectively.…”
Section: Discussionmentioning
confidence: 99%